Public Relations Strategy of the Directorate General of PSDKP in Socializing the Utilization and use of the Vessel Monitoring System (VMS) - Ananda Marcell Dinofa; Ayu Larasati; Nur Rakhma Novika; Oko Marisno (Journal of Creative Power and Ambition (JCPA), 2026)
This study analyzes the communication strategy of the Public Relations Division of the Directorate General of Marine and Fisheries Resources Surveillance (Ditjen PSDKP) in socializing the Vessel Monitoring System (VMS) to fishing vessel owners and fisheries business operators. Using a qualitative case study approach, data were gathered through participant observation, semi-structured interviews with PR staff, and documentation of socialization activities. Data analysis involved reduction, presentation, and conclusion drawing. The findings reveal that the PR Division employed an integrated communication strategy utilizing digital media, social media, mass media, face-to-face communication, public outreach forums, and exhibitions to engage diverse audiences. A two-way communication approach enhanced public understanding of VMS functions, benefits, and importance while fostering participatory government-public relationships. The study concludes that a well-planned communication strategy, supported by appropriate media selection and effective message delivery, significantly contributes to VMS socialization effectiveness and strengthens Ditjen PSDKP's institutional image as an informative and responsive government agency.